PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHERE (TPS) DENGAN MENGGUNAKAN MEDIA GAMBAR DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS TERPADU DI SMP NEGERI 15 PALU - Basirun, Basirun (Katalogis, 2017)
This study aimed to obtain information about (1) how the implementation of cooperative learning model Think Pair Share (TPS) using media images in social studies class VII SMPN 15 Palu. (2) Does the application of cooperative learning model Think Pair Share (TPS) using media images can increase the motivation to learn social studies in class VII SMPN 15 Palu. (3) Is the application of the model of cooperative learning Think Pair Share (TPS) using media images can improve learning outcomes in class IPS VIISMPN 15 Palu. (4) What is the response of students to the application of the model of cooperative learning Think Pair Share (TPS) using media images in social studies class VII SMPN 15 Palu. The method used is a qualitative descriptive method. The population of as many as 269 students of SMP Negeri 15 Palu. Total sample of 60 people using Proportional sampling techniques. Data collection techniques using a questionnaire Likert scale models, observation, interview and documentation. The data analysis technique that is the first data reduction, data presentation, and draw conclusions. The results showed that: First, adoption of cooperative learning model Think Pair Share (TPS) using media images in social studies were carried out in class VII SMPN 15 Palu can be said to be going well with the percentage value of 97 teacher activity and the value of the percentage of activity 76 students with good criterion. Second, the motivation of students in learning by using media techniques image by 80 with high criteria, this is due to the establishment of the atmosphere of a different class than usual during the learning. Third, the method of learning through media images TPS significant effect on student learning outcomes, the results of the data analysis by classical absorption capacity of 71 students with very good criteria and is categorized as complete although there are some students who scored still carried an average of 75. Fourth , the results of research that has been conducted in SMP Negeri 15 Palu in class VII, obtained the results of student feedback regarding the application of learning models using the image of 81 with both criteria. It is not independent of the contribution of teachers and the use of media used in learning so that the response given good student.